(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
Let B_2n denote the Brualdi-Li matrix, and let ρ_2n=ρ(B_2n) denote the Â Perron value of the Â Brualdi-Li matrix of order 2n. We prove that is Â monotonically decreasing for all